MODEL PEMBELAJARAN KADIR (KONEKSI, APLIKASI, DISKURSUS, IMPROVISASI, REFLEKSI) BERBANTUAN PHET SIMULATION: DAMPAK TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK - Oktavia, Yovi; Kadir, Kadir; Farida, Farida; Andriani, Siska (ALGORITMA: Journal of Mathematics Education, 2023)
AbstractThe purpose of this study was to find the impact of KADIR learning model assisted by PhET Simulation on mathematical critical thinking skills. The research was conducted in a public high school in Bandar Lampung. This research is a quasi-experiment with a sample of 4 X MIPA classes, involving 144 students. The sample was determined using cluster random sampling technique. Data collection of mathematical critical thinking skills using tests, then analyzed with one-way ANOVA. The results revealed that the average mathematical critical thinking ability of students taught with the KADIR learning model assisted by PhET Simulation (80.64) was higher than the Discovery Learning model assisted by PhET Simulation (63.33) KADIR model (62.67) and Discovery Learning model (58.78). The KADIR learning model assisted by PhET Simulation has an effect on students' mathematical critical thinking skills (F = 37.68; p-value = 0.000; n2 = 0.81). The conclusion of this study is that integrating PhET Simulation in the KADIR learning model is effective or has an impact on improving students' mathematical thinking skills.  AbstrakTujuan penelitian ini adalah untuk menemukan dampak model pembelajaran KADIR berbantuan PhET Simulation terhadap kemampuan berpikir kritis matematis. Penelitian dilaksanakan di suatu SMA Negeri di Bandar Lampung. Penelitian ini adalah kuasi eksperimen dengan sampel 4 kelas X MIPA, melibatkan 144 peserta didik. Sampel ditentukan menggunakan teknik cluster random sampling. Pengumpulan data menggunakan tes, dan dianalisis dengan ANOVA satu jalan. Hasil penelitian mengungkapkan bahwa rata-rata kemampuan berpikir kritis matematis peserta didik yang diajar dengan model pembelajaran KADIR berbantuan PhET Simulation (80,64) lebih tinggi daripada model Discovery Learning berbantuan PhET Simulation (63,33)  model KADIR (62,67) dan model Discovery Learning (58,78). Model pembelajaran KADIR berbantuan PhET Simulation berpengaruh terhadap kemampuan berpikir kritis matematis peserta didik (F = 37,68; p-value = 0,000; n2 = 0,81). Kesimpulan penelitian ini adalah bahwa dengan mengintegrasikan PhET Simulation pada model pembelajaran KADIR ternyata efektif atau berdampak terhadap peningkatan kemampuan berpikir  matematis peserta didik.